CONTRASTIVE ANALYSIS OF RELIGIOSITY IN AMERICAN AND POLISH PROVERBS FROM A LINGUOCULTURAL PERSPECTIVE - Kochman-Haładyj, Bożena (Proverbium - Yearbook, 2017)
The purpose ascribed to this paper is to compare and contrast the corpus of selected American and Polish religion-related paremias – featuring God as a constitutive element – with a view to revealing cer-tain distinctive features in the attitude towards religiosity in two respec-tive linguo-cultures. Hence, principally, the God-related proverbs from both languages are analysed by the use of the semantic approach and grouped in terms of the general messages they put across in order to search for common ground and specific differences. A secondary ob-jective to be reached is an attempt at explanation of the most apparent peculiarities bearing in mind different places of proverb origin and their specific geographical, historical, social and cultural environments. In case of religion—but not exclusively—a paremiographical col-lection of the proverbs of a given nation constitutes an ethnography of the people, which if systematized can provide a profound insight into people’s, among others, philosophy and beliefs, moral truths and social values. Such a universally acknowledged axiom is underscored by an English philosopher Francis Bacon who said that The genius, wit, and spirit of a nation are discovered in its proverbs (Trench 2003, 46). The relation between language and culture is the most prominent postulate behind a contemporary scholarly discipline integrating linguistics and the study of culture called Linguistic Culturology. The pilot empirical section of the paper is based on two unparal-leled and invaluable paremiographical collections. The American reli-gion-related proverbial texts including the component of ‘God’ are selected from A Dictionary of American Proverbs (1992) edited by Wolf-gang Mieder, Stewart A. Kingsbury, and Kelsie B. Harder. In turn, the analytical research on Polish God-related proverbs is conducted on the basis of a fairly recent and detailed paremiographical reference com-piled by Danuta and Włodzimierz Masłowski in their Wielka Księga Przysłów Polskich ‘A big book of proverbs’ (2008).